Pengaruh Intensitas Menonton Channel Youtube Reza Oktovian dan Pengawasan Orang Tua terhadap Perilaku Agresif yang dilakukan Remaja Sekolah Menengah Pertama - Aryatama Wibawa, Michael; Pradekso, Tandiyo (Interaksi Online, 2018)
Based on the data of communication and information ministry, there are 322 casese about violence in teenager triggered by the social media and internet in 2014 and the cases are still increasing compared to 100 cases in 2011. Youtube is one of the social media platform that mostly accesed by Indonesian people by 49%. Social learning theory and parental mediation theory are used in this case. Respondents are Junior High School teenagers aged 14-15 years old who are also Reza Oktovian Youtube channel subscribers. Based on the regression analysisi test to the intensity variable of watching Reza Oktovian Youtube Channel (X1) to the verbal agressive attitude to the teenagers (Y), the determination coefficient result is 31,7%, while the parental guide (X2) to the teenagers aggresive attitude (Y), the determination coefficient result is 36,6% eith the significance rate = 0,000 means > significance criteria (0,05). It means the regression model the variable effect of X to Y is high and signicancy between variable based on the research is very significant. Therefore it show that there are some effect between the intensity of watching Reza Oktovian youtube channel and the parental guide to the aggresive attitude which are done by teenagers. The higher intensity in watching Reza Oktovian youtube channel, the higher aggresive attitude by teenagers, in the other hand, the higher parental guide, the lower aggresive attitude by teenagers.